MAPPING THE DISTRIBUTION OF MANGROVE BY REMOTE SENSING IN THE COASTAL OF KARAWANG REGENCY - Pasaribu, Roberto Patar; Pranoto, Aris Kabul; Sewiko, Roni; Afwafiah, Elfa (Asian Journal of Aquatic Sciences, 2022)
Mangrove forest areas are generally found throughout the coast of Indonesia and grow in locations that have a tidal influence. At this time the condition of mangroves both qualitatively and quantitatively continues to decline from year to year. The decline in the quality of mangroves is a serious concern along with the shrinking of its area. The purpose of this study was to determine the condition and extent of mangrove distribution on the coast of Karawang Regency. The research was carried out on the coast of Karawang Regency from March to June 2021. The research method was carried out by survey methods and satellite data collection, to obtain field condition data and Landsat 8 satellite imagery data. Image data processing and analysis was carried out using the NDVI (Normalized Difference Vegetation Index) method which can create a boundary between mangrove and non-mangrove. With this method, it can be seen the changes in the mangrove distribution area from year to year. The results of data processing and analysis show that in 2013 the distribution of mangroves on the coast of Karawang Regency has an area of ​​207.88 km2, in 2016 it has an area of ​​357.22 km2 and in 2020 its area is 237.61 km2.